Experimental and Numerical Study to Determine the Relationship between Tensile Strength and Compressive Strength of Concrete - Badarloo, Baitollah; Kari, Amir; Jafari, Faezeh (Salehan Institute of Higher Education, 2018)
As one of the most widely used materials in different structures, concrete is a material evaluated and categorized based on compressive strength criterion. In addition, national and international codes (INBC- part 9) and standards determine the tensile strength of concrete based on its compressive strength. The purpose of this research is to determine the relationship between compressive strength and tensile strength of C20, C30 and C40 grades. In this laboratory research, a total of 42 cubic specimens of 150 × 150 × 150 mm and 42 cylindrical specimens of 300 × 150 mm were assessed under compressive and tensile tests, respectively. Based on the results of this study, the relationships presented in Ninth Article of Iranian National Building Codes, ACI-318 and Euro Code 2 have been evaluated.